Case Report: Modified surgery combined with photodynamic therapy for treating basal cell carcinoma in special facial regions - Fan, Zhixia; Lv, Chao; Suo, Panpan; Shi, Lei; Miao, Guoying (Frontiers in Oncology, 2025)
Basal cell carcinoma (BCC) is one of the most common malignant skin tumors, predominantly occurring in sun-exposed areas such as the head and face. The combination of surgery and photodynamic therapy (PDT) enables rapid tumor clearance and comprehensive regional treatment of cancerous tissues, effectively reducing recurrence rates. This report presents two cases of patients with basal cell carcinoma in special facial areas treated with modified surgical excision combined with photodynamic therapy.